Zoisova literarna republika Vloga pisma v narodnih prerodih Slovencev in Slovanov - Vidmar, Luka (Studia litteraria, 2010)
The book deals with the correspondence of Žiga Zois Baron Edelstein, the most important Enlightenment-era patron and mentor of Slovenian poets, writers, and scholars. The first part of the book defines the position of Zois' correspondence within the history and the genre of the letter. The second part examines its importance for Slavic national revivals. Zois' network at the end of the 18th and in the beginning of the 19th centuries linked into Enlightenment-era Republic of Letters the greatest intellectuals of the Central Europe and the Balkans. With the centers in Ljubljana and Vienna it did not only instructed Slovenian writers and scholars, but also supported all Slavic cultural nationalisms in Austrian empire.